2018
DOI: 10.1186/s40359-018-0271-y
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy intervention in cardiac autonomic modulation, anxiety, and depression in mothers of preterms: randomized controlled trial

Abstract: BackgroundMothers of preterm infants often have symptoms of anxiety and depression, recognized as risk factors for the development of cardiovascular diseases and associated with low rates of heart rate variability (HRV). This study aimed to evaluate the influence of music therapy intervention on the autonomic control of heart rate, anxiety, and depression in mothers.MethodsProspective randomized clinical trial including 21 mothers of preterms admitted to the Neonatal Intensive Care Unit of a tertiary hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 30 publications
3
53
1
24
Order By: Relevance
“…As tabelas 2 e 3 apresentam as pontuações e percentuais de homens e mulheres para depressão e ansiedade obtidos a partir da administração dos inventários BDI-I e IDATE-T e E. Foi observada correlação positiva e estatisticamente significativa entre os níveis de ansiedade-estado e ansiedade-traço no público analisado (p=0,00, r=0,75). A sobreposição entre ansiedade traço/estado e ansiedade/depressão aparece na literatura, uma vez que se tratam de marcadores sintomatologicamente afins (Oliveira et al, 2006;Brito, 2011;Ribeiro et al, 2018).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…As tabelas 2 e 3 apresentam as pontuações e percentuais de homens e mulheres para depressão e ansiedade obtidos a partir da administração dos inventários BDI-I e IDATE-T e E. Foi observada correlação positiva e estatisticamente significativa entre os níveis de ansiedade-estado e ansiedade-traço no público analisado (p=0,00, r=0,75). A sobreposição entre ansiedade traço/estado e ansiedade/depressão aparece na literatura, uma vez que se tratam de marcadores sintomatologicamente afins (Oliveira et al, 2006;Brito, 2011;Ribeiro et al, 2018).…”
Section: Resultsunclassified
“…Diante do exposto, assim como dos valores de estatística descritiva dos dados de ansiedade e depressão, é possível inferir que a alostasia mental do público em questão existe, e se relaciona com a presença de marcadores autonômicos cardiovasculares dentro do esperado para o público em estudo (Camm, 1996;Thomas & Viljoen, 2019). Isso confirma que uma boa variabilidade da frequência cardíaca pode se relacionar a uma boa saúde mental (Ribeiro et al, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…It affects alpha waves in the brain, resulting in reduced anxiety and stress and increased relaxation (Varisoglu & Güngör Satilmis, 2020). A study focused on the relationship between music and depression and anxiety and found that mothers who underwent music intervention had significantly reduced depression and anxiety levels (Ribeiro et al., 2018). Reduced stress and anxiety promote more release of the hormone oxytocin and prolactin and increase milk production (Varisoglu & Güngör Satilmis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…En el área afectivo-emocional, Rickson y Gold, citados en Benedito (2010) (14) , observaron resultados positivos disminuyendo la tensión y mejorando la autoestima; en el área de la comunicación, incrementando la capacidad de expresarse y la creatividad; en el área social, aumentando la conciencia social; en el área cognitiva, incrementando la atención, aprendizaje y memoria reciente; en el área fisiológica, produciendo efectos similares al éxtasis y otro tipo de drogas en nuestro cerebro. En este mismo sentido se pronuncian Oslé (2011) (15) , Ribeiro et al (2018) (16) , Fernández et al (2018) (17) y Marins et al (2018) (18) .…”
Section: Musicoterapia Como Complemento Terapéuticounclassified